Placental T2* estimated by magnetic resonance imaging and fetal weight estimated by ultrasound in the prediction of birthweight differences in dichorionic twin pairs. (March 2019) - Poulsen, Sofie Sondrup; Sinding, Marianne; Hansen, Ditte Nymark; Peters, David A.; Frøkjær, Jens B.; Sørensen, Anne
Abstract: Introduction: Intertwin birthweight (BW) difference is associated with an increased risk of adverse outcome. Ultrasound estimated fetal weight (EFW) is the current method to predict intertwin BW difference, however, the sensitivity is poor. Therefore, new methods are needed. Placental T2* estimated by magnetic resonance imaging (MRI) provides non-invasive information about the placental function. This study aimed to investigate placental T2* difference as a new predictor of BW difference, and to compare it to the EFW. Methods: We included 25 dichorionic twin pairs at 19–38 weeks' gestation. Placental T2* was obtained by MRI and EFW by ultrasound. Correlations between each predictor and BW difference were examined by simple linear regression, and the combined model was analyzed by multiple linear regression and likelihood ratio test. Results: Strong positive correlations were demonstrated between intertwin differences in placental T2* and BW (r = 0.80, p < 0.005), and EFW and BW (r = 0.64, p < 0.005). Placental T2* difference was a strong independent predictor of BW difference (p < 0.001), and the combined model performed better than each predictor alone (p < 0.0001). Discussion: This pilot study demonstrates that placental T2* difference may be a predictor of intertwin BW difference irrespectively of fetal size. The clinical potential of this method deserves further investigation in a larger clinical study Highlights: Intertwin birthweight difference is associated to a high risk of adverse outcome. Placental T2* provides non-invasive information about the placental function. Intertwin placental T2* difference correlates to intertwin birthweight difference. Placental T2* may be used in the prediction of intertwin birthweight difference.